2017
DOI: 10.21767/2574-2825.1000016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planned Health Educational Program on Menstrual Knowledge and Practices among Adolescent Saudi Girls

Abstract: Objectives: To assess knowledge, practices and quality of life of adolescent Saudi girls regarding menstruation and menstrual self-hygienic care. To find the relation between knowledge, practices and selected variables of quality of life of adolescent Saudi girls regarding menstruation and menstrual self-hygienic care. To evaluate the outcome and impact of health education program on knowledge and practices of adolescent Saudi girls regarding menstruation and menstrual self-hygienic care.Methods: An experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
3
2
0
Order By: Relevance
“…[25] Regarding the medical and obstetric data, the age of menstruation, the present study findings revealed that the mean age of Damietta group was 13.4 ± 1.4 while the mean age of menstruation of Port Said was 11.1 ± 1.2. These findings are in agreement with several previous studies [27][28][29][30] in which the authors mentioned that mostly sixty-seven percent of the girls were well prepared and aware about menstruation.…”
Section: Discussionsupporting
confidence: 93%
“…[25] Regarding the medical and obstetric data, the age of menstruation, the present study findings revealed that the mean age of Damietta group was 13.4 ± 1.4 while the mean age of menstruation of Port Said was 11.1 ± 1.2. These findings are in agreement with several previous studies [27][28][29][30] in which the authors mentioned that mostly sixty-seven percent of the girls were well prepared and aware about menstruation.…”
Section: Discussionsupporting
confidence: 93%
“…Nurses can undertake the role of a health educator and mentor through proper approaches in correcting genital hygienic practice skills (18 and 30) . (2017) (38) who showed that slightly more than one quarter of adolescents had satisfactory menstrual practice score level These results match with Emam W.…”
Section: Concerning Students' Present Historysupporting
confidence: 81%
“…Results: (23 -24) . (2017) (38 ) and Ibrahim H and Esmail M (2019) (39) who stated that only one fifth of adolescent girls had good level of knowledge regarding menstruation before implementation of educational program compared to the majority of them had good level of knowledge after program.…”
Section: C-implementation Phasementioning
confidence: 99%
“…8,9 Similarly in the study of Pokhrel S et al the use of sanitary pad increased to 90.8%, followed by new cloth (6.6%) and old cloth (2.6%) in Posttest (P-Value <0.001). 11 Mean score before health talk was 3.64 and score was 5.18 after the talk was noted in this study. Total score was ranged between 0-6.…”
Section: Discussionsupporting
confidence: 59%